The Neutralization of Religious Dissonance - Dunford, Franklyn W. (Review of religious research, 1973)
This paper deals with the creation and resolution of dissonance within a religious community. The purpose is to explore dissonance reduction by means of the techniques of neutralization developed by Sykes and Matza in an attempt to explain Sunday shopping by people who accept such activity as violation of "divine law." Analysis suggests that two of the techniques are rather extensively utilized to justify Sunday shopping activity. They are the "denial of responsibility" and the "appeal to higher loyalties." In this study these techniques relate to an ancient Christian value which suggests that the law of the Sabbath is superseded under certain circumstances. This value allows committed church members, on the one hand, to accept unequivocally the admonitions of their leaders against Sunday shopping, and, on the other hand, to engage in the sanctioned activity.